2020
DOI: 10.1074/jbc.ra119.011546
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution crystal structures of two prototypical β- and γ-herpesviral nuclear egress complexes unravel the determinants of subfamily specificity

Abstract: Herpesviruses uniquely express two essential nuclear egress-regulating proteins forming a heterodimeric basic structure of the nuclear egress complex (core NEC). These core NECs serve as a hexameric lattice-structured platform for capsid docking and recruit viral and cellular NEC-associated factors that jointly exert nuclear lamina- and membrane-rearranging functions (multicomponent NEC). Here, we report the X-ray structures of β- and γ-herpesvirus core NECs obtained through an innovative recombinant expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(97 citation statements)
references
References 32 publications
3
84
0
Order By: Relevance
“…Our initial data derived from coexpression experiments with domain swap constructs, in which distinct parts of the hook element were artificially exchanged between HCMV and EBV (pUL53::BFLF2 fusions), indicated that very little variability in the hook element is acceptable for retaining a detectable level of high-affinity interaction with the respective groove proteins. In most cases of domain swap, the autologous hook element lost reactivity in NEC interaction [16]. A third aspect considered as potentially facilitating nonautologous NEC interaction was seen in the recruitment of a number of NEC-associated host proteins, a property known for all herpesviral NECs analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our initial data derived from coexpression experiments with domain swap constructs, in which distinct parts of the hook element were artificially exchanged between HCMV and EBV (pUL53::BFLF2 fusions), indicated that very little variability in the hook element is acceptable for retaining a detectable level of high-affinity interaction with the respective groove proteins. In most cases of domain swap, the autologous hook element lost reactivity in NEC interaction [16]. A third aspect considered as potentially facilitating nonautologous NEC interaction was seen in the recruitment of a number of NEC-associated host proteins, a property known for all herpesviral NECs analyzed so far.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a colocalization of HSV-1 proteins pUL34 and pUL31 with VZV Orf24 and Orf27, respectively, was detectable ( Figure 4D, d and h). In contrast, nonautologous combinations between homologs of the different herpesviral subfamilies did not develop colocalization ( Figure 4D, u and y; Figure 4E) [16]. The nonautologous colocalization between HCMV and MCMV nuclear egress proteins was additionally quantitated.…”
Section: Addressing the Question Of Crossviral Recruitment Of Nec Promentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the currently available data on core NEC structures, four 3D crystal structures have been published, i.e., those of HCMV, HSV-1, PRV and EBV [16,18,20,[22][23][24]. Many structural properties of core NEC proteins were found conserved and qualitatively mostly consistent.…”
Section: Comparison Of Primary Sequences and Structural Properties Bementioning
confidence: 99%